Climate change-related knowledge and attitudes among a sample of the general population in Egypt - Salem, Marwa Rashad; Hegazy, Nelly; Thabet Mohammed, Anas Abdullnasser; Mahrous Hassan, Esraa; Saad Abdou, Mohamed Mohyeldin; Zein, Marwa M. (Frontiers in Public Health, 2022)
Introduction : Identifying the public awareness and risk perception regarding climate change, are fundamental preliminary steps in determining gaps and paving the way for awareness campaigns that address climate change causes and counteraction mitigation measures. However, few studies were conducted in Egypt; thus, the researchers conducted the current cross-sectional study among a sample of the Egyptian population to identify general knowledge and perception about climate change and its effects, as well as attitudes toward mitigation measures. Methods: An exploratory population-based electronic-open survey, was conducted among 527 members of the general population between January and April 2022, using a convenience sampling technique. A pre-tested 2-page (screen) electronic included three sections: sociodemographic characteristics, global warming/climate change-related knowledge, and attitude toward climate change mitigation. Results The average global warming knowledge score was 12 3.Global warming mean knowledge score was 12 ± 3. More than 70% (71.1%) of the participants were knowledgeable (percentage score greater than 70%). Approximately half of the enrolled participants (48.2%) agreed that everyone is vulnerable to the effects of global warming/climate change. More than three-quarters (78.3%) of the participants agreed that carbon emissions from vehicles and industrial industries methane emissions were the first factors that contributed contribute to climate change, followed by the ozone holes (731%). Global warming/climate change-related knowledge was statistically higher in participants aged of >30 years, married participants, urban residents, highly educated individuals, and employed individuals highly educated, and employed (p-value ≤ 0.05). Approximately 80% of the participants agreed that responding to the questionnaire drew their attention to the topic of climate change and its effects. More than two-thirds of those polled agreed that increasing public transportation use could help mitigate the effects of climate change/global warming, followed by the materials used and the direction of construction. Conclusion: More than two-thirds of the participants were knowledgeable regarding climate change. Social media and the internet were the main sources of information . However,; however, participants need to had to must get the information in a different way that could help in helped helps changing their attitude positively toward the issue of climate change mitigation.